2021
DOI: 10.1155/2021/9999612
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ferroptosis and Its Role in Type 2 Diabetes Mellitus

Abstract: Ferroptosis is a novel form of nonapoptotic regulated cell death (RCD). It features iron-dependent lipid peroxide accumulation accompanied by inadequate redox enzymes, especially glutathione peroxidase 4 (GPX4). RAS-selective lethal 3 (RSL3), erastin, and ferroptosis inducing 56 (FIN56) induce ferroptosis via different manners targeting GPX4 function. Acyl-CoA synthetase long-chain family 4 (ACSL4), lysophosphatidylcholine acyltransferase 3 (LPCAT3), and lipoxygenases (LOXs) participate in the production of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 118 publications
(178 reference statements)
0
91
0
Order By: Relevance
“…It has become appreciated recently that necrotic cell death is not always accidental and can instead occur downstream of regulated signaling events. Such types of regulated necrosis are lytic forms of cell death that can drive inflammation and immune responses following plasma membrane rupture and the release of cellular cargo into the extracellular Ferroptosis is a form of regulated necrosis that is iron-dependent and characterized by lipid peroxidation that occurs due to insufficient redox enzyme activity, particularly glutathione peroxidase 4 (GPX4) [260,262]. A recent study revealed that the treatment of human islets with the ferroptosis-inducing agent erastin leads to a reduction of islet cell viability, and that this could be prevented by cotreatment with an iron chelator [259].…”
Section: β-Cell Regulated Necrosismentioning
confidence: 99%
“…It has become appreciated recently that necrotic cell death is not always accidental and can instead occur downstream of regulated signaling events. Such types of regulated necrosis are lytic forms of cell death that can drive inflammation and immune responses following plasma membrane rupture and the release of cellular cargo into the extracellular Ferroptosis is a form of regulated necrosis that is iron-dependent and characterized by lipid peroxidation that occurs due to insufficient redox enzyme activity, particularly glutathione peroxidase 4 (GPX4) [260,262]. A recent study revealed that the treatment of human islets with the ferroptosis-inducing agent erastin leads to a reduction of islet cell viability, and that this could be prevented by cotreatment with an iron chelator [259].…”
Section: β-Cell Regulated Necrosismentioning
confidence: 99%
“…Mitochondria are the most abundant organelles in cardiomyocytes, which are mainly responsible for energy metabolism ( Li N. et al, 2020 ); meanwhile, cardiomyocyte as an important source of energy, if its mitochondrial function deteriorates, it would lead to myocardial I/R injury. The double membranes structure of mitochondria provides an ideal location for ferroptosis, and some researchers have observed mitochondrial impairment in patients with ferroptosis ( Sha et al, 2021 ). After ferroptosis, excess intracellular free iron can enter the mitochondria, resulting in smaller myocardial mitochondria, increased mitochondrial membrane density, decreased mitochondrial respiration, and mitochondrial membrane potential depolarization ( Abdalkader et al, 2018 ; Sumneang et al, 2020 ), thus inducing CD and a series of Cardiac Diseases such as arrhythmia ( Hu et al, 2021 ).…”
Section: The Mechanism Of Ferroptosismentioning
confidence: 99%
“…So far, many factors participate in the production of lipid peroxides such as Acyl-CoA synthetase long-chain family 4 (ACSL4), lysophosphatidylcholine acyltransferase 3 (LPCAT3), and lipoxygenases (LOXs). 43 ACSL4 is a member of the long-chain acyl coenzyme A synthase family (ACSLs), which is a class of essential enzymes involved in fatty acid metabolism. 44 LPCAT3 is a protein that catalyzes the reacylation of lysophospholipids to phospholipids.…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%